PENGARUH KOMUNIKASI PEMASARAN TERINTEGRASI DAN EKUITAS MEREK TERHADAP LOYALITAS NASABAH (STUDI PADA PT. BANK SUMUT CABANG SIDIKLANG) - Bintang, Joice Saputri; Sutrisna, Endang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
research was conducted at PT. Bank SUMUT Sidikalang Branch located at Sisingamangaraja street No. 172 Sidikalang. Problems in this research is the number of customers who experience fluctuations within the last 5 years and an increasing number of customers who close the account at PT. Bank SUMUT Branch Sidikalang .The purpose of this study is to determine the effect of integrated marketing communications and brand equity to customer loyalty at PT. Bank SUMUT Sidikalang Branch. In this research data analysis used is descriptive and quantitative with SPSS program. Samples in the study amounted to 100 respondents from the population calculated by the formula Taro Yamane, with the method of sampling using purposive sampling. Data collection techniques used are primary and secondary data through observation, questionnaires and interviews. Data analysis method used is simple linear regression analysis and multiple linear regression method.From the results of tests conducted show that integrated marketing communications and brand equity have a positive and significant impact on customer loyalty at PT. Bank SUMUT Sidikalang Branch.Key word: Integrated marketing communications, brand equity and customer loyalty